2010
DOI: 10.1002/cyto.b.20549
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of degranulation and cytokine production in natural killer cells from spondyloarthritis patients at single-cell level

Abstract: Background: A pathogenetic role of natural killer (NK) cells has been hypothesized in spondyloarthritides (SpA), but still conflicting data exist. Aim of this study was to investigate, in a cohort of SpA patients, the peripheral blood NK cell number, the cytokine production (IFNc and TNFa), and the cytotoxic activity on target cell stimulation. Moreover, we aimed to evaluate the expression of KIR3DL1, an inhibitory receptor binding HLA class I alleles, including HLA-B27 strongly associated with SpA, between di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Similarly, polymorphisms within the HLA-Bw4 may undermine recognition by KIR3DL1 [ 127 ]. Increases in KIR3DL1 have been associated with diseases such as HIV and spondyloarthritis [ 66 , 128 ]. KIR genes have previously been investigated in CFS patients where frequency of KIR3DS1 was significantly elevated in the CFS patients in comparison to the non-CFS group [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, polymorphisms within the HLA-Bw4 may undermine recognition by KIR3DL1 [ 127 ]. Increases in KIR3DL1 have been associated with diseases such as HIV and spondyloarthritis [ 66 , 128 ]. KIR genes have previously been investigated in CFS patients where frequency of KIR3DS1 was significantly elevated in the CFS patients in comparison to the non-CFS group [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has also shown a decrease in IFNγ producing NK cell subset with normal NK cell degranulation in patients with AS [24]. In CIA mice model protective role of IFNγ producing NK cells was reported as NK cell depletion (IFNγ producing) resulted in increased IL-17 production by Th17 cells [29].…”
Section: Discussionmentioning
confidence: 93%
“…Low perforin expressing NK cells have been reported previously in RA and systemic onset JIA. Further using functional assay reduced cytotoxicity has been seen in patients with SoJIA as well as RA [9,20,21,23,24]. A recent study on AS using degranulation assay also reported impaired NK cell cytotoxicity [24].…”
Section: Discussionmentioning
confidence: 95%
“…The strong association between NK cells and the aetiology of AS is underlined by the capability of the disease-dependent elevated killer cell immunoglobulin-like receptors (KIRs) to recognise the HLA-B27 antigen, which is expressed in 80–90% of AS patients [ 48 , 49 ]. Concomitant with a pathogenetic upregulated frequency of KIR3DL1 + NK cells in AS, interferon (IFN)γ production is correspondingly diminished [ 50 ]. Moreover, activated KIR3DL2 + NK cells are increased in SpA and may play a pathogenic role.…”
Section: Discussionmentioning
confidence: 99%